Perang Jawa dan Kegiatan Penerjemahan (1825-1830) - Rusyeni, Rini (Jurnal Penerjemahan, 2018)
One of the Dutch Historians argued that the Java War aggravated due to the poor quality of Javanese language ability of the government civil servants. (Fasseur, 1997:91) This article aims to describe the mistranslation activities committed by translators who worked for the colonial government in the period of 1825-1830 that might serve as the proofs of Fasseur’s argument on the Java War. In the article, there is an explanation of the situation during the Java war and the analysis of a sample of translation of a letter regarding Diponegoro taken from the book written by Roorda van Eysinga, Handboek den Land en Volkenkunde, Geschiedtaal, Aardrijks, Staatkunde van Nederlands Indie (1842). The conclusion is that although the translators applied faithful method and cultural equivalent strategy for the translations, they made some mistakes in their translations. The mistakes, thus, caused misunderstanding for the readers. These misunderstandings could have lead to bigger conflict between the Javanese and the Dutch in the Java War. Keywords: Java war, translations, Javanese language, Dutch Colonial Government, Dutch language